A Case of a Combined Hamartoma of the Retina and RPE Concurrently Found in the Same Eye as Peripheral Astrocytic Hamartomas. (September 2019) - Sherman, Stefanie D.; Schechet, Sidney A.; Shapiro, Michael J.; Blair, Michael P.
We report a case of a 7-year-old boy with neurofibromatosis 2 who was referred to our pediatric retina clinic for deteriorating vision of his left eye. Fundoscopy revealed a gray epiretinal and vitreous opacity extending to the fovea in the left eye. Optical coherence tomography (OCT) demonstrated an epiretinal membrane (ERM) with a distinct tissue plane and overlying vitreoretinal strands, consistent with combined hamartoma of the retina and retinal pigment epithelium (CHRRPE). Intraoperative OCT-guided pars plana vitrectomy and membrane peel were performed and the tissue was sent for histopathologic evaluation. Intraoperative scleral-depressed examination also revealed multiple elevated, white-gray, semitranslucent masses near the ora serrata, consistent with astrocytic hamartomas. Histopathologic analysis of the epiretinal tissue revealed glial origin. Recognition of any of these lesions in a young patient should prompt neurologic and genetic evaluation.